Rapid Hip Osteoarthritis Development in a Patient with Anterior Acetabular Cyst with Sagittal Alignment Change - Yasuhiro Homma; Tomonori Baba; Nobuhiko Sumiyoshi; Hironori Ochi; Hideo Kobayashi; Mikio Matsumoto; Takahito Yuasa; Kazuo Kaneko (Case Reports in Orthopedics)
Rapidly destructive coxarthrosis (RDC) is rare and develops unusual clinical course. Recent studies suggest multiple possible mechanisms of the development of RDC. However the exact mechanism of RDC is still not clear. The difficulty of the study on RDC is attributed to its rareness and the fact that the data before the onset of RDC is normally unavailable. In this report, we presented the patient having the radiographic data before the onset who had rapid osteoarthritis (OA) development after contralateral THA, which meets the current criteria of RDC. We thought that the increased posterior tilt of the pelvis after THA reinforced the stress concentration at pre-existed anterior acetabular cyst, thereby the destruction of the cyst was occurred. As a result the rapid OA was developed. We think that there is the case of rapid osteoarthritis developing due to alternating load concentration by posterior pelvic tilt on preexisting anterior acetabular cyst such as our patient among the cases diagnosed as RDC without any identifiable etiology. The recognition of sagittal alignment changes and anterior acetabular cyst may play important role in prediction and prevention of the rapid hip osteoarthritis development similar to RDC.